PENGARUH OVERCONFIDENCE DAN HERDING BIAS TERHADAP KEPUTUSAN INVESTASI SAHAM PADA MASA PANDEMI COVID-19 YANG DIMODERASI OLEH MEDIA SOSIAL - Bintoro, Ellen (Media Akuntansi dan Perpajakan Indonesia, 2022)
The study aims to investigate: 1) the effect of overconfidence on stock investment decision making during the Covid-19 pandemic, 2) the effect of herding bias on stock investment decision making during the Covid-19 pandemic, 3) the effect of overconfidence on stock investment decision making with stock recommendations on social media as a moderating variable during the Covid-19 pandemic, and 4) the effect of herding bias on stock investment decision making with stock recommendations on social media as a moderating variable during the Covid-19 pandemic. Dummy variables are used to represent stock recommendation factors on social media. A questionnaire is used as main data in this investigation. This study's sample size was 100 stock-investing students from the Faculty of Management and Business at the University of Ciputra. In this research, multiple linear regression analysis and MRA moderation regression analysis are used to evaluate hypotheses using SPSS version 22 software. This study indicates that overconfidence has a positive effect on stock investment decision making, herding bias has a positive effect on stock investment decision making, stock recommendations in social media do not moderate the effect of overconfidence on stock investment decision making, and stock recommendations in social media moderate the effect of herding bias on stock investment decision making. Keywords: overconfidence, herding bias, stock recommendation, social media, stock investment decision, Covid-19.